2020
DOI: 10.3390/ijms21051815
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Signaling Repressor LlDELLA1 Controls the Flower and Pod Development of Yellow Lupine (Lupinus luteus L.)

Abstract: Precise control of generative organ development is of great importance for the productivity of crop plants, including legumes. Gibberellins (GAs) play a key role in the regulation of flowering, and fruit setting and development. The major repressors of GA signaling are DELLA proteins. In this paper, the full-length cDNA of LlDELLA1 gene in yellow lupine (Lupinus luteus L.) was identified. Nuclear-located LlDELLA1 was clustered in a second phylogenetic group. Further analyses revealed the presence of all conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…For years, there has been a hypothesis that the reason for excessive ower separation may be incorrect stamen development, and as a consequence insu cient pollination, fertilization, and pod setting, which nally reduces yield. Our earlier study has shown that changing level of LlDELLA1 mRNA, encoding major repressors of GA signaling, supports the correct ower and pod development [34]. Interestingly, the expression of LlDELLA1 in the closed-ower bud phase is relatively high and then slightly decreased until the anther opening, while during pollination, fertilization and early pod development the gradual increase of transcript level is observed.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…For years, there has been a hypothesis that the reason for excessive ower separation may be incorrect stamen development, and as a consequence insu cient pollination, fertilization, and pod setting, which nally reduces yield. Our earlier study has shown that changing level of LlDELLA1 mRNA, encoding major repressors of GA signaling, supports the correct ower and pod development [34]. Interestingly, the expression of LlDELLA1 in the closed-ower bud phase is relatively high and then slightly decreased until the anther opening, while during pollination, fertilization and early pod development the gradual increase of transcript level is observed.…”
Section: Introductionmentioning
confidence: 81%
“…Changes in the yellow lupine anther structure during dehiscence program Dehiscence of anther is a multistage process which was examined in such species as A. thaliana, O. sativa, Zea mays, Nicotiana tabacum and Solanum lycopersicum [4]. In our previous study we showed that yellow lupine anther opening takes place in the fourth stage of ower development [34]. Therefore, it seems interesting to study the process of late anther development and the accompanying alterations in tested species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations